Protection of Students’ Privacy Rights in Online Education Under the Personal Data Protection Act (PDPA) - kampong, wachira (Chalermkarnchana Academic Journal, 2025)
This research aims to study the protection of students’ personal rights in online education under the Personal Data Protection Act B.E. 2562 (PDPA). It analyzes the implementation of the law, students’ and educators’ awareness levels, and educational institutions’ measures to safeguard students’ personal data. The study employs qualitative research and doctrinal legal research methods, examining legal documents, institutional practices, and case studies of online learning platforms. The findings indicate that while PDPA provides clear personal data protection principles, its practical enforcement in online education remains limited. Educational institutions lack clear consent procedures and effective data protection measures. The research also found that students and educators have a moderate to low understanding of PDPA, and some online learning platforms do not fully comply with personal data protection principles. The study suggests developing specific guidelines for educational institutions, improving consent mechanisms, and providing training programs to enhance PDPA awareness among students and faculty members.